2013
DOI: 10.18632/oncotarget.1510
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase-3β inhibition depletes the population of prostate cancer stem/progenitor-like cells and attenuates metastatic growth

Abstract: Cancer cells with stem or progenitor properties play a pivotal role in the initiation, recurrence and metastatic potential of solid tumors, including those of the human prostate. Cancer stem cells are generally more resistant to conventional therapies thus requiring the characterization of key pathways involved in the formation and/or maintenance of this malignant cellular subpopulation.To this end, we identified Glycogen Synthase Kinase-3β (GSK-3β) as a crucial kinase for the maintenance of prostate cancer st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 50 publications
5
35
1
Order By: Relevance
“…Furthermore, the average fluorescent densities of these cells verified the morphological observations in accordance with previous studies by Visegrady et al [34]. Other authors found that reduced integrin-mediated adhesion was attributed to the disturbance of F-actin (formed by β-actin) and was responsible for prostate cancer stemness and bone metastasis [32]. …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, the average fluorescent densities of these cells verified the morphological observations in accordance with previous studies by Visegrady et al [34]. Other authors found that reduced integrin-mediated adhesion was attributed to the disturbance of F-actin (formed by β-actin) and was responsible for prostate cancer stemness and bone metastasis [32]. …”
Section: Discussionsupporting
confidence: 89%
“…In gene function studies, the specific knockdown or upregulation of target genes without affecting other gene products is an important method for developing specific mutants for use in lentiviral packaging vectors [30-32]. In view of the vital function of ABCE1 in protein synthesis, translation termination and ribosome recycling, knockdown of ABCE1 may interfere with basic cellular metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that stable inhibition of GSK-3 isoforms leads to selection for different cell subsets or types, or changes the proportions of precursor cells in the population. Consistent with this possibility, small molecule inhibition of GSK-3 was recently reported to deplete the population of prostate cancer stem/progenitor-like cells in PC3 and PC3M cells, as measured by the proportion of ALDH HIGH cells and reduced expression of stem/progenitor markers including NANOG and OCT4 [28]. However, this was not observed in LNCaP C4-2 and DU145 cells.…”
Section: Discussionmentioning
confidence: 73%
“…Several other spots were reproducibly altered with stable GSK-3α silencing, namely an increase in binding to the Sp1 binding site (row 11 columns 1/2), the Stat5/6 binding site (columns 13/14) and the Pbx1 binding site (row 7 columns 15/16), also observed upon acute silencing of GSK-3α. To address the possibility that stable inhibition of GSK-3 leads to selection for prostate cancer stem/progenitor-like cells, as was recently reported for PC3 cells [28], we measured the expression levels of three genes expressed in 22Rv1-derived stem/progenitor cells, SOX2, NANOG and BCRP [29], in the 22Rv1-derived cell clones. This revealed small reductions in expression of SOX2 in both GSK- 3-isoform silenced cell lines, a small increase in NANOG expression in the GSK-3α-silenced cell line and no change in expression of BCRP (Figure 1E).…”
Section: Resultsmentioning
confidence: 99%